Alterações cognitivas em ratos infectados com Toxoplasma gondii - Maia, Raquel da Silveira (2012)
Toxoplasma gondii is a protozoan parasite that induces behavioral changes in rodents. The aim of this study was to evaluate the effect of infection by T. gondii during the chronic phase in working memory and impulsivity in rodents as well as the effect of antipsychotics to reverse any behavioral changes resulting from infection. Female Wistar rats (n = 40) were infected with 25 cysts of the strain ME-49 T. gondii after 4 months the animals were subjected to behavioral tests: tolerance to delay gratification, in which the animal must choose between two rewards, a smaller and more immediate, but delayed and the test of spontaneous alternation, in which the animal must use spatial cues to remember previously visited arms. Antipsychotic drugs were intraperitoneally administered during the testing of the behavioral experiments, the antipsychotic is haloperidol (1.5 mg / kg) administered 60 min before the start of the session and the antipsychotic clozapine (2.5 mg / kg) 30 min before. Animals infected with the parasite did not show operating deficits of memory, and motor impairment did not develop, however motor impairment was observed only in animals treated with haloperidol. It was found that administration of clozapine and haloperidol increased the percentage of alternation in infected and control groups in task switching espontânea.Não no distinction between control animals and infected the test of tolerance to delay gratification in relation to the percentage of choices greatest reward, during the pre-training and training, in which there is a delay of 15 s to access the great reward, however it was observed that infected animals prefer the greatest reward, when there is a delay of 30 s when compared to control group. The administration of clozapine possible that infected animals chose the greatest reward in the delay of 30 seconds during the test. These data suggest that infected mice do not exhibit deficits in working memory and that clozapine has therapeutic efficacy in improving cognitive performance of mice infected